Retirement and Life Satisfaction - Schmitt, Neal; White, John Kenneth; Coyle, Bryan W.; Rauschenberger, John (Academy of Management Journal, 1979)
Demographic, personality, and job related correlates of life satisfaction and satisfaction with retirement associates, work and activities, and finances are reported for recently retired Civil Service employees. Health was found to be an important determinant of satisfaction in retirement. Satisfaction with previous job and the perception of being forced to leave work also were related to satisfaction in retirement. Self-esteem and locus of control were significantly correlated with retirement satisfaction, and particularly with overall life satisfaction.